Development of Eu2+ and Mn2+ co-activated silicate phosphor for plant cultivation light source. (24th May 2019) - Kunimoto, Takashi; Fujita, Yoshiko; Kajiyama, Hiroshi; Honma, Tetsuo; Kawaguchi, Hideki; Ishigaki, Tadashi; Ohmi, Koutoku; Ohshima, Kentaro; Miyazaki, Daisuke; Saito, Yu; Hara, Shigeo; Sakurai, Takahiro; et al.
Abstract: Various light sources for plant production have been developed to establish a completely controlled factory. We propose a pulse light source using Xe discharge. For the rapid growth of the plant, an intense light covering the absorption spectral region of chlorophyll is demanded, and periodic irradiation is also required because the photosynthetic reaction has a certain period. In this study, Sr3 MgSi2 O8 :Eu, Mn phosphor powders with various Eu and Mn content, which show two emission peaks in the absorption region of photosynthetic pigment and phytochrome, were synthesized, and were analyzed using X-ray diffraction, photoluminescence and electron spin resonance spectroscopy. It was found that the exchange-coupled Mn-Mn and Eu-Mn pairs lead the rapid decay of Mn emission and efficient energy transfer from Eu and Mn ions, respectively. A plasma tube array panel using the phosphor was also fabricated and the similar emission spectrum of Sr3 MgSi2 O8 :Eu, Mn is obtained under vacuum-UV excitation in comparison to the UV excitation.